Get Busy with Skippyjon Jones - Schachner, Judith Byron
Join Skippyjon Jones and his imagination for all kinds of fun in this new sticker activity book. Readers will love spotting the differences, making their way through mazes, creating doodles, finishing sticker puzzles, and much more in this bright, busy book. Packed with fantastico things to make and do, it's a must-have for all El Skippito fans and is sure to keep every little chihuahua busy!